THE OPTIMIZATION IN DEEP DRILLING IN CONSIDERATION WITH RESTRICTION TO TORQUE VALUE - P.P. VERESCHTIN; E.N. GAVRILOVA; A.D. LUKJANOV; V.M. SCHERBACOV (Advanced Engineering Research)
The question of optimization in deep drilling under the adaptive control system with restriction to torque value in drill is considered.